The Use of Problem Based (PBL) Learning in Teaching Reading - Zulkifli Zulkifli (Universitas Hamzanwadi, 2017)
This study was aimed at examining the effectiveness of Problem-Based Learning (PBL) in Teaching Reading. This study belongs to a pre experimental research. The population of this study was all the eighth grade students of SMPN 1 Selong which consisted of nine classes with 302 students. However the researcher just took one class as a sample of the study and there were 34 students in this class. To get the data, the researcher used the research instrument namely objective test in the form of multiple choice tests. Furthermore, in analyzing the data, the researcher used SPSS 17.00 for windows. Based on the obtained data, the mean score of pre-test was 6.78 and the mean score of the post-test was 10.34.Iit means that, there was a difference between the mean score in pre-test and post-test. In testing hypothesis, the researcher found that t value (df= 33) = 16.216, p = 0.000. It showed that the value of significant level (p value) was lower than 0.05. Therefore, the alternative hypothesis was accepted. This data showed that problem-based learning was effective in teaching reading for the eighth grade students of SMPN 1 Selong.